Pendidikan : metode pembelajaran inklusi tingkat SD/ MI - Yassaro, Fierly Sabila (Maliki Interdisciplinary Journal, 2025)
Inclusive education is one of the strategic steps in realizing equal quality education for children with special needs (ABK). Through inclusive education, every child has the same right to access proper education without discrimination. The Indonesian government has mandated public schools to accept students with special needs as a form of implementing equitable education policies. However, the success of inclusive education greatly depends on the readiness of schools to adapt their curriculum, learning methods, and the competence of educators who are able to understand the individual needs of students. Therefore, synergy between the government, educators, and the community is needed to create a learning environment that is friendly, supportive, and inclusive for all students. Inclusive education is not only a fulfillment of basic rights, but also an important investment in creating a generation of citizens who are fair and competitive.